The Calcium Binding Protein S100A11 and Its Roles in Diseases - Zhang, Linqiang; Zhu, Tingting; Miao, Huilai; Liang, Bin (Frontiers in Cell and Developmental Biology, 2021)
The calcium binding protein S100 family in humans contains 21 known members, with each possessing a molecular weight between 10 and 14 kDa. These proteins are characterized by a unique helix-loop-helix EF hand motif, and often form dimers and multimers. The S100 family mainly exists in vertebrates and exerts its biological functions both inside cells as a calcium sensor/binding protein, as well as outside cells. S100A11, a member of the S100 family, may mediate signal transduction in response to internal or external stimuli and it plays various roles in different diseases such as cancers, metabolic disease, neurological diseases, and vascular calcification. In addition, it can function as chemotactic agent in inflammatory disease. In this review, we first detail the discovery of S100 proteins and their structural features, and then specifically focus on the tissue and organ expression of S100A11. We also summarize its biological activities and roles in different disease and signaling pathways, providing an overview of S100A11 research thus far.